Pemetaan Wilayah Berdasarkan Indikator Pemerataan Pendidikan menggunakan Biplot di Sumatera Utara - Sri Zulhayana (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Equal distribution of education is a strategic issue in national development, including in North Sumatra Province. However, the reality on the ground shows that there are significant disparities in terms of access and quality of education between districts/cities in North Sumatra. To overcome this problem, a comprehensive mapping effort is needed on the condition of education in each district/city in North Sumatra. Biplot analysis is a multivariate statistical technique that is very useful for visualizing complex relationships between many variables and objects in a two-dimensional graph. Biplot analysis was chosen in this research because of its ability to present complex data visually and easily understood. This research aims to: 1) Map regions based on indicators of educational equality using biplot analysis. 2) Identify regional groups that have different educational characteristics. The data source for this research is secondary data obtained from Badan Pusat Statistik (BPS) of North Sumatra Province. The data used are Average Years of Schooling (RLS), Expected Years of Schooling (HLS), Primary/equivalent School Enrollment Rates (APM SD), Middle School/Equivalent Enrollment Rates (SMP APM), High School Enrollment Rates (APM SD). High School APM), Higher Education Participation Rate (APM PT). Next, this data is used as a variable in the research as x1, x2, x3, x4, x5, and x6. The research results present information from Biplots obtained by Regency/City which can be divided into 4 quadrants. And from the results of the analysis, it was found that the most dominant characteristics were the variables of average length of schooling and Expected Years of Schooling.